Bio Efficacy of Certain Insecticides against Chilli Aphid, Aphis Gossypii Glovers - B. Prasad, M. Kumar*, M. Chinamen, Ok. Monoroma and (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: Bio efficacy of seven insecticides with different concentration viz., Endosulfan (0.07%), Monocrotophos (0.05%), Malathion (0.05%), Dimethoate (0.04%), Phosalone (0.04%), Cypermethrin (0.01%) and Neem oil (3.5%) was evaluated against aphid, Aphis gossypii (Glover) on chilli, Meitei morok Capsicum annum L. Among the insecticides, the best result was obtained with Malathion (0.05%) and Phosalone (0.04%), but Neem oil (3.5%) was found least effective in reducing Aphis gossypii population.